Extended capability of the integrated transport analysis suite, TASK3D-a, for LHD experiment. (18th September 2017) - Yokoyama, M.; Seki, R.; Suzuki, C.; Sato, M.; Emoto, M.; Murakami, S.; Osakabe, M.; Tsujimura, T.Ii.; Yoshimura, Y.; Ido, T.; Ogawa, K.; Satake, S.; et al.
Abstract: The integrated transport analysis suite, TASK3D-a (Analysis), has been developed to be capable for routine whole-discharge analyses of plasmas confined in three-dimensional (3D) magnetic configurations such as the LHD. The routine dynamic energy balance analysis for NBI-heated plasmas was made possible in the first version released in September 2012. The suite has been further extended through implementing additional modules for neoclassical transport and ECH deposition for 3D configurations. A module has also been added for creating systematic data for the International Stellarator–Heliotron Confinement and Profile Database. Improvement of neutral beam injection modules for multiple-ion species plasmas and loose coupling with a large-simulation code are also highlights of recent developments.